2022
DOI: 10.4174/astr.2022.102.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and improvement of Enhanced Recovery After Surgery protocols for colorectal cancer surgery

Abstract: Purpose Enhanced Recovery After Surgery (ERAS) reduces postoperative complications and shortens hospital stays. We aimed to describe the implementation and improvement of ERAS protocols in our institution through a multidisciplinary team approach. Methods A multidisciplinary team comprised of colorectal surgeons, anesthesiologists, nurses, pharmacists, nutritionists, and a performance improvement team was launched to develop the ERAS protocol. The ERAS protocol was foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…However, on the contrary, different compliance rates of patients undergoing ERAS in our study did not show significant differences in patient outcomes 20 , 24 . Seow-En et al .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, on the contrary, different compliance rates of patients undergoing ERAS in our study did not show significant differences in patient outcomes 20 , 24 . Seow-En et al .…”
Section: Discussioncontrasting
confidence: 84%
“…Our study follows a study conducted in Korea by Choi et al . 20 , who concluded that the implementation of the ERAS protocol from 2017 to 2019 at St. Mary’s Hospital in patients undergoing colon surgery showed significant results at a shorter length of stay with an average of 5.1 days. This study evaluated more ERAS protocol components than our study.…”
Section: Discussionmentioning
confidence: 99%
“…Audits play an important role, especially in detailed and procedural analyses, because implementing new protocols is often problematic over time, 37 , 38 , 39 and these problems can encourage a return to traditional or familiar practices. For example, in this study, the ERAS items that showed good adherence were usually items that were already being practiced before starting the protocols, such as advising patients and providing antibiotic prophylaxis before scalp incision.…”
Section: Discussionmentioning
confidence: 99%
“…Additional-ly, one study was conducted in a foreign country and another did not include details about the ERAS protocol, leading to their exclusion. Finally, the remaining 16 studies were analyzed [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Table 1 presents the authorship status of anesthesiologists in these studies, along with the inclusion of ERAS items related to the field of anesthesiology.…”
Section: Current Status Of Eras In South Koreamentioning
confidence: 99%